Sustainable value chain financing for smallholder agricultural production in the Philippines (Philippine Journal of Development, 2022)
Cognizant of the value, contribution, and challenges in the country’s agricultural finance, the government has intensified its lending programs to help the sector, particularly smallholders, thus, boosting affordable and easy access retail lending in recent years. Despite these efforts, however, significant problems remain, including the lack of markets and low prices, which have had significant implications on the overall repayment capacity and credit rating of small farmers and fisherfolk in the Philippines. Indeed, lending programs are unlikely to become successful if financing and production are not viewed in the bigger context of value chain financing. This paper looks into the farmers and fisherfolk’s financing ecosystem and provides recommendations on how the existing value chain financing in the Philippines can become more inclusive and sustainable for them.